On the Suslin Number of Totally-Bounded Left-Topological Groups - Protasov, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For every infinite cardinal α, we construct a zero-dimensional totally-bounded left-topological group with Suslin number α.